The WHO’s communication strategies on social media during the early stage of the 2021 COVID vaccination campaign - Poch-Butler, Santana Lois (2023)
The crisis caused by COVID-19 forced public and private actors to deploy various strategies on social media to communicate effectively with their public. This research analyses the institutional communication of the World Health Organization’s Twitter account during the first quarter of 2021, with the aim of shedding light on their strategy and analyzing both its strengths and the areas with room for improvement in a crisis like the one studied. For this purpose, an ethnographic content analysis was run on the tweets published by the institutional account of the WHO and the responses issued by the public. A computer-assisted analysis was undertaken through two software programs (SPSS 27 and NVivo 11), and an online tool, Onodo – that helped us develop a sociogram with the different relationships between the actors involved in the crisis and risk communication of the WHO around the subject of vaccination. The main results show, on the one hand, that vaccination is not the focal point of the WHO’s discourse at a time when the public’s interest was centered on said thematic axis, and on the other, that the organization was not able to create an effective dialogic space. Considering these findings, a reflection is encouraged to optimize professional praxis in future risk and crisis communication strategies in digital environments, expanding the scope of this study towards other organizations and/or time frames.